Taliban and Afghanistan; a Systematic Literature Review - Fisher Zulkarnain; Muhammad Salman Abidin; Putri Habibah Abidin (UIN Sunan Gunung Djati, 2023)
This systematic literature review aims to enhance our understanding of the Taliban activities in Afghanistan and broaden our knowledge of the associated phenomenon. We employed a Systematic Literature Review protocol and sourced our data from the Scopus index, yielding 164 articles from which 91 were selected following a filtration process. Our analysis reveals that the resurgence of the Taliban and its organizational dynamics over the past four decades have had a significant impact on Afghanistan and its citizens. The majority of the studies in our dataset (52 articles) approached the phenomenon from a political perspective, with health issues being the second most explored topic (17 articles). The data collected in this study indicates that the majority of the literature discussing the Taliban and Afghanistan was qualitative in nature (89 articles). Our results suggest that the Taliban's current influence in Afghanistan is only weakly linked to religious motivations, contrary to the common media portrayal. Only a small number of studies in our dataset (3.29%, n=3) explored the ideological basis of the phenomenon. This paper underscores the need for further research to address the pressing political and health issues faced by the Afghan people and highlights the potential benefits of improved political stability and increased access to healthcare facilities.// // // // //